A tantárgy-pedagógiák szerkezete, megítélésük kritériumai - Bárdos, Jenő (Magyar Pedagógia, 2012)
This paper explains how the content structure of language pedagogy can serve as a pattern in describing and evaluating methodologies in teaching other subjects. The approach is deductive and embraces the levels of the theory of education (generic level); theory of instruction (specific level); and the structure of various content pedagogies such as teaching history, mathematics, music, etc. (concrete or actual level). Awareness of the methodology of content pedagogies will include the complete cultural history of methods, approaches, and techniques ever used in the teachingof the subject in question (diachronic view) and the state of the art in contemporary methodology (synchronic view), offering an integrative and comparative approach to the particular profession. Pedagogical actions are considered to be interactive acts of communication, in which the input (selection and arrangement of teaching material), the educational environment (context, situation, methods and the human factor), and the output (results) are systematically assessed and evaluated (feedback). All subject-centred methodologies (or content-based pedagogies such as teaching biology, literature, art, etc.) will share (and contribute to) a common taxonomy used as a set of criteria in evaluating the potential for their development and maturity.